Analysis of the results of staging decompression / stabilization interventions in the treatment of patients with tandem stenosis of cervical and lumbar spine - V. V. Shepelev; V. A. Byvaltsev; A. A. Kalinin; V. A. Sorokovikov; A. V. Krutko (Acta Biomedica Scientifica)
The concept of "tandem stenosis" comprises combination of degenerative stenosis in both cervical and lumbar spine. At the moment, there is no consistent approach to the surgical procedures in this group of patients, as well as the researchers do not pay much attention in their papers to the sequence and stage-by-stage approach to the procedures and to the analysis of combined surgical procedures. The aim of the research was to analyze the results of staging decompression/ stabilization interventions in the treatment of patients with tandem stenosis of cervical and lumbar spine. We performed a retrospective analysis of prospectively collected results of treatment of 46 patients with combined (tandem) stenosis of cervical and lumbar spine. The patients were operated in four neurosurgical clinical units of Vladivostok, Irkutsk and Novosibirsk. We assessed clinical data: level of pain syndrome - using visual analog scale (VAS), neck disability index (NDI), Oswestry disability index (ODI), MacNab and Nurick clinical outcomes, as well as the results of plain spine radiography and neuroimaging studies (MRI, MSCT). Multicenter study of the results of staging surgical procedures with the use of specialized microsurgical instruments in the treatment of patients with tandem stenosis of cervical and lumbar spine allowed us to confirm their high clinical and radiological effectiveness.